Empathy in Korean medical students: Findings from a nationwide survey. (3rd October 2015) - Park, Kyung Hye; Roh, Hyerin; Suh, Dae Hun; Hojat, Mohammadreza
Abstract: Background : Previous studies on empathy in Korean medical students were conducted on small populations or with different scales of measurement, resulting in low representativeness and generalisability of the findings. Aim : To evaluate empathy in Korean medical students throughout the country and to make suggestions to improve empathy. Methods : The Jefferson Scale of Empathy (JSE) (Korean) was used, and the impact of sex, age, the medical school admission system, and grade of the respondents was investigated. Results : We analyzed 5343 questionnaires and found a mean empathy score of 105.9 ± 12.8. Females and post-baccalaureate students had higher scores as compared with their counterparts. There was a significant difference between the admission systems after controlling for gender. Students from higher grade levels had lower scores than those from the lower grade levels. Conclusions : The JSE score of Korean medical students was lower than that of students in Western countries. The difference of gender and medical school admission system should be considered, and capability to apply empathy to clinical practice should be focused upon in medical training.